2009
DOI: 10.1210/me.2009-0041
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacochaperone-Mediated Rescue of Calcium-Sensing Receptor Loss-of-Function Mutants

Abstract: The calcium sensing receptor (CaSR) is a Family C/3 G protein-coupled receptor that translates changes in extracellular Ca(2+) into diverse intracellular signals. Loss-of-function mutations in human CaSR cause familial hypocalciuric hypercalcemia and neonatal severe hyperparathyroidism. CaSR must navigate a number of endoplasmic reticulum quality control checkpoints during biosynthesis, including a conformational/functional checkpoint. Here we examine the biosynthesis of 25 CaSR mutations causing familial hypo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
61
1

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(71 citation statements)
references
References 47 publications
9
61
1
Order By: Relevance
“…This supports the proposed notion that even if the CASR mutant itself may not be responsive to calcimimetics, the remaining normal CASR allele in FHH or in heterozygous NHPT could confer sensitivity to calcimimetic treatment in vivo (86). In addition, calcimimetics may act as pharmacological chaperones to rescue misfolded inactivating mutants (87,88,89). The polymorphic variants A986S and R990G occur in about 24% and 4% of healthy adults respectively and lead to slight changes in ionized serum calcium levels (90).…”
Section: Effect Of Calcimimetics In Vitro On Mutations Causing Loss Osupporting
confidence: 74%
“…This supports the proposed notion that even if the CASR mutant itself may not be responsive to calcimimetics, the remaining normal CASR allele in FHH or in heterozygous NHPT could confer sensitivity to calcimimetic treatment in vivo (86). In addition, calcimimetics may act as pharmacological chaperones to rescue misfolded inactivating mutants (87,88,89). The polymorphic variants A986S and R990G occur in about 24% and 4% of healthy adults respectively and lead to slight changes in ionized serum calcium levels (90).…”
Section: Effect Of Calcimimetics In Vitro On Mutations Causing Loss Osupporting
confidence: 74%
“…19). We have previously shown that NPS R-568 can rescue both WT CaSR and some loss-of-function mutants identified in familial hypocalciuric hypercalcemia/ neonatal severe primary hyperparathyroidism patients, increasing both total and plasma membrane-targeted levels of receptor protein and function (21,22). Allosteric agonists may have similar effects in vivo because uremic rats treated with cinacalcet (54) as well as first/second generation allosteric agonists (calcimimetics) NPS R-568 (55), Amgen R-568 (56, 57), or AMG-641 (58) show reduced parathyroid gland hyperplasia, vascular calcification, and remodeling as a result of both enhanced activation and expression of CaSR in relevant tissues (54 -58).…”
Section: Discussionmentioning
confidence: 99%
“…Point mutations in the WT FLAG-CaSR background (E837I, A843E, and L849P) were generated as described previously (22). The CaSR/mGluR1␣ CT chimera was generated by incorporating a silent PvuI restriction site at the proposed junction in both CaSR and mGluR1␣ constructs, digesting each vector with PvuI, followed by ligation.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Several studies reported that the calcimimetic 3-(2-chlorophenyl)-N-[(1R)-1-(3-methoxyphenyl)ethyl]propan-1-amine (NPS R-568) improves the signal transduction characteristics of loss-of-function polymorphic variants of the human CaSR associated with human disease (Rus et al, 2008;Lu et al, 2009;White et al, 2009). NPS R-568 is structurally very similar to cinacalcet, and therefore one would expect cinacalcet to have similar effects on those polymorphic receptors, and, vice versa, one would expect NPS R-568 to have effects similar to those of cinacalcet and calindol on the polymorphic receptors studied here.…”
Section: Discussionmentioning
confidence: 99%